2013
DOI: 10.1080/00071668.2013.793295
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different histidine sources and zinc supplementation of broiler diets on dipeptide content and antioxidant status of blood and meat

Abstract: 1. The objective of this study was to investigate how a diet containing spray-dried blood cells (SDBC) (4%) with or without zinc (Zn) would affect the concentration of two histidine heterodipeptides and the antioxidant status of broiler blood and breast muscles. 2. The study was carried out on 920 male Flex chickens randomly assigned to 4 dietary treatments: I - control, II - diet I with SDBC, III - diet I with SDBC and supplemented with Zn and IV - diet I supplemented with L-histidine. Birds were raised on fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…According to this reasoning, free l ‐histidine would be the rate‐limiting precursor for HCD synthesis in broilers, in contrast to horses and humans, where β ‐alanine has been clearly identified as the rate‐limiting precursor. Attempts have been made in the past to increase broiler muscle carnosine and anserine concentrations through either l ‐histidine or β ‐alanine supplementation in the diet . Feeding broilers a diet low in l ‐histidine (at 67% of the requirements) resulted in considerably lower anserine levels in muscle, and carnosine was no longer detected .…”
Section: Discussionmentioning
confidence: 99%
“…According to this reasoning, free l ‐histidine would be the rate‐limiting precursor for HCD synthesis in broilers, in contrast to horses and humans, where β ‐alanine has been clearly identified as the rate‐limiting precursor. Attempts have been made in the past to increase broiler muscle carnosine and anserine concentrations through either l ‐histidine or β ‐alanine supplementation in the diet . Feeding broilers a diet low in l ‐histidine (at 67% of the requirements) resulted in considerably lower anserine levels in muscle, and carnosine was no longer detected .…”
Section: Discussionmentioning
confidence: 99%
“…The research results of Ogata (2002) and Kasaoka et al (2004) also confirmed that the supplementation of L-histidine, βalanine, or carnosine to diets significantly boosted broiler growth. Kopec et al (2013b) stated that the supplementation of 4% spray-dried blood cells (SDBC), with or without Zn, with 0.22% of histidine to broiler feed, influenced broilers' performance and the antioxidative status of meat. The research results of Hu et al (2009) showed that broiler performances and feed conversion were not influenced by supplementation of carnosine to feed.…”
Section: Discussionmentioning
confidence: 99%
“…Higher carnosine contents were recorded in the meat of chickens fed porcine blood cells and blood meal. Kopec et al (2013b) used four treatments: control, SDBC, SDBC + Zn, and supplemented L-histidine, and found the following concentrations of carnosine in breast muscles, respectively: 0.891, 1.060, 0.905, and 1.205 mg/g tissue. In comparison to other groups, the best results were obtained in the group with supplemented L-histidine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In broilers, histidine levels in plasma and breast muscle were increased by dietary histidine. However, levels were low if compared to the increase of the dipeptides carnosine and anserine (Ishibashi et al., ; Haug et al., ; Kai et al., ) or not strongly increased (Kopeć et al., ). In turkeys, no increase of histidine level in breast muscle was observed after supplementation (Kopec et al.…”
Section: Assessmentmentioning
confidence: 99%